2018
DOI: 10.1002/hpm.2503
|View full text |Cite
|
Sign up to set email alerts
|

Administrative reform and pay‐for‐performance methods of primary health service delivery: A comparison of 3 health districts in Cambodia, 2006‐2012

Abstract: Since 1999, performance-based financing or pay-for-performance (P4P) methods have been piloted in the Cambodian public health sector, first as one part of external contracting approaches with international nongovernment organizations and from 2009 as a part of internal contracting arrangements between units within the Ministry of Health under a wider public sector administrative reform. This study analyses these reforms and compares outcomes in 3 health districts. The study analysed routine quantitative data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The majority of the studies that we identified had a cross-sectional design and were conducted in a range of settings. Our sample included a study based in a subnational area of Nigeria 32 ; a study on a national level in Afghanistan that analyzed changes in health system performance over a 5-year period 33 ; a study based in 3 districts of Cambodia reporting on implementation of an initiative centered around performance-based financing 34 ; a study based in a subnational area of India that evaluated a well-established health management information system 35 ; and an evaluation based in Côte d’Ivoire assessing change in quality, availability, and use of data following an intervention that aimed to improve RHIS performance. 36 In addition, there was 1 randomized controlled trial set in Uganda that examined the effectiveness of a community monitoring intervention by comparing communities that received the intervention with communities that did not.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of the studies that we identified had a cross-sectional design and were conducted in a range of settings. Our sample included a study based in a subnational area of Nigeria 32 ; a study on a national level in Afghanistan that analyzed changes in health system performance over a 5-year period 33 ; a study based in 3 districts of Cambodia reporting on implementation of an initiative centered around performance-based financing 34 ; a study based in a subnational area of India that evaluated a well-established health management information system 35 ; and an evaluation based in Côte d’Ivoire assessing change in quality, availability, and use of data following an intervention that aimed to improve RHIS performance. 36 In addition, there was 1 randomized controlled trial set in Uganda that examined the effectiveness of a community monitoring intervention by comparing communities that received the intervention with communities that did not.…”
Section: Resultsmentioning
confidence: 99%
“…Leadership and the role of active engagement from senior management was highlighted across multiple included studies as a feature associated with strengthened M&E capacity and facilitating uptake at the local level. 33 , 34 , 38 , 40 , 41 The concept of leadership is itself nuanced and difficult to measure and is represented slightly differently in each of the studies. In the study by Holvoet and Inberg, 38 which compared Rwandan and Ugandan health systems, there was evidence demonstrating the role of leadership in both countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations